PHYSICAL DEPOSITION OF COATINGS IN VACUUM - Urinov N. F.; Saidova M. Kh.; Sobirov M. B. (American Journals Publishing, 2024)
The article presents the process of fphysical deposition of coatings in a vacuum, which consists of spraying a substance in a special vacuum chamber. As well as the main operations of a typical technological process for applying coatings using the PVD method.
Keywords: Physical deposition, coating, vacuum, ionization, magnetron sputtering, ion beam, electron beam.